2007
DOI: 10.1007/s11237-007-0021-3
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced variations in the size of nanoparticles of CdS in colloidal solutions

Abstract: The possibility of decreasing the size of colloidal nanoparticles of CdS in the oxidative photocorrosion reaction in the presence of methylviologen and of increasing their size during photocatalytic reduction of sulfur in ethanol in the presence of cadmium acetate. A dependence of the quantum yield of the latter reaction on the initial size of CdS nanoparticles was observed, which was interpreted as a result of quantum size effects.The unique luminescent, non-linear optical and photochemical properties of semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The photocatalytic reduction of elemental sulfur by alcohol on the surface of CdS nanoparticles in the presence of cadmium acetate leads to the deposition of an additional amount of CdS on it and to an increase in the average size of the nanoparticles [245]. It is seen from Fig.…”
Section: Photoinduced Increase Of the Size Of Semiconductor Nanopartimentioning
confidence: 83%
See 1 more Smart Citation
“…The photocatalytic reduction of elemental sulfur by alcohol on the surface of CdS nanoparticles in the presence of cadmium acetate leads to the deposition of an additional amount of CdS on it and to an increase in the average size of the nanoparticles [245]. It is seen from Fig.…”
Section: Photoinduced Increase Of the Size Of Semiconductor Nanopartimentioning
confidence: 83%
“…The method proposed in [69,70] for improving the electrical contact between the TiO 2 nanoparticles in the films by irradiating them after additional treatment with Ti IV complexes may prove to be of great practical importance. Of greatest importance, however, are the methods of reducing and increasing the size of the semiconductor nanoparticles examined in Section IV and also the approaches to narrowing the size distribution of the nanoparticles [230][231][232][233][234][235][236][237][238][239][240][241][242][243][244][245][250][251][252][253][254][255][256].…”
Section: Photochemical Change Of the Characteristics Of The Synthesizmentioning
confidence: 99%
“…It is known that S 8 can be reduced photocatalytically by alcohol at the surface of CdS [9] and TiO 2 [10] nanoparticles. Comparison of the data set out above with these data gives reason to suppose that photocatalytic reduction of S 8 , followed by the formation of CdS, also occurs in this case: It was established that the quantum yield of the formation of cadmium sulfide F varies in the range of 0.02-0.03 with increase in the content of ZnO nanoparticles from 1·10 -3 to 1·10 -2 M and hardly depends at all on either the initial concentrations of Cd(CH 3 COO) 2 and S 8 or their ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The rod-like crystals of ZnO probably fulfill the role of a unique template for the forming tubes, ensuring invariability in the geometry of the space in which photodeposition of the cadmium sulfide occurs. In [9] it was shown that CdS itself is capable of acting as a photocatalyst for the reduction of sulfur. However, if the formation of cadmium sulfide occurred not only at the zinc oxide but also at the previously deposited CdS, disruption of the directional growth of the nanotubes and distortion of their regular form would be expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation